Hubungan Komunikasi Terapeutik Perawat dengan Tingkat Kecemasan pada Anak Usia Prasekolah di Ruang St. Theresia Rumah Sakit Elisabeth Medan Tahun 2024 - Rotua Elvina Pakpahan; Amnita Ginting; Erti Hidayat Zebua (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Children commonly experience anxiety during hospitalization, especially when they are unfamiliar with the clinical environment. Therapeutic communication serves as an essential nursing skill that can reduce this anxiety and help young patients feel more secure. This study examines the relationship between nurses’ therapeutic communication abilities and the anxiety levels of hospitalized preschool children. Using a quantitative cross-sectional design, the research involved 48 participants selected through complete sampling, with data collected using structured questionnaires. Therapeutic communication was measured using a nurse communication assessment tool, while the Spence Children’s Anxiety Scale (SCAS) Preschool version was used to evaluate anxiety levels. The findings revealed that 22 respondents (45.8%) perceived nurses’ therapeutic communication as very poor, and 18 children (37.5%) showed moderate anxiety. Statistical analysis using the Spearman rank correlation test produced a p-value of 0.002 (p < 0.05), demonstrating a significant negative relationship between nurses’ therapeutic communication and anxiety levels among preschoolers at Santa Elisabeth Hospital Medan in 2024, with a correlation coefficient of 0.440. These results suggest that implementing structured training programs in therapeutic communication could enhance nurses’ ability to provide supportive and anxiety-reducing care for young patients.